The shape of non-graviton operators for SU(2) - Sunjin Choi; Seok Kim; Eunwoo Lee; Jaemo Park (Journal of High Energy Physics)
Abstract The BPS spectrum of AdS/CFT exhibits multi-gravitons at low energies, while having black hole states at higher energies. This can be studied concretely in AdS5/CFT4 in terms of classical cohomologies, even in the quantum regimes at finite 1/N. Recently, Chang and Lin found a threshold for non-graviton states in the SU(2) maximal super-Yang-Mills theory. We explicitly construct and present this threshold cohomology.